Memoria colectiva de la parroquia de Pomasqui :mitos y leyendas - Yánez Santos, Santiago David (2017)
The collective memory of the settlers expressed through stories or stories that are transmitted by word of mouth through language, constitutes a total image. The oral tradition is going to be the succession of a story that is included in the life of a collectivity with permanence that is transmitted by generations, passed by the mark of time and the presence of inheritances that give historical testimony. The objective of this work is to inform about the myths and legends through the oral memory of the inhabitants of Pomasqui; are narrated stories of actors who talk about the history of this Parish, with stories or versions told by the authors themselves, who talk about historical, social, political and literary themes. On the other hand, to collect information on the myths and legends of Pomasqui, the work was done using research methods taken from Rosana Guber's book "The Metropolitan Savage", using techniques such as interview, non-directive interview, in-depth interview And systematization. The work of "Collective memory of the Parish of Pomasqui: Myths and Legends", was organized by categories, according to the general concepts, raised by the theories of the authors Levi Strauss and Pascuala Margan, about the myths and legends.